Study on China’s 2030 provincial carbon quota allocation scheme considering the positive and negative effects of historical emissions - Liu, Chuanwang; Lei, Yalin; Chen, Wenhui; Jiang, Yong (Frontiers in Environmental Science, 2024)
The carbon quota allocation scheme serves as the fundamental backbone for ensuring the smooth and sustainable operation of the carbon market. Despite numerous prior studies, ongoing debates persist regarding the impact of historical emissions, both positive and negative, on carbon quota allocation. Utilizing the four indicators of historical emissions (both positive and negative), egalitarianism, payment capability, and emission efficiency, this paper employs the entropy method to develop 22 distinct carbon quota allocation plans tailored for China's provincial regions in the year 2030. Subsequently, utilizing the shadow price method, the study calculates the emission reduction costs of each province under each allocation scheme, thereby evaluating the carbon quota plans from the perspective of emission reduction costs. Finally, a comparative analysis is conducted to assess the impact of both positive and negative historical emissions on the carbon quota allocation scheme, and the paper identifies the carbon quota allocation approach that minimizes the overall emission reduction cost for China. The findings suggest that:(1) allocating more allowances to provinces with higher historical emissions can effectively reduce emission reduction costs for each province; (2) the most cost-effective option for carbon quota allocation is a scheme that takes into account both egalitarian and historical emission criteria;(3) in order to further decrease the overall cost of emissions reduction, it is crucial to achieve comprehensive coverage of the carbon market and facilitate inter-provincial carbon quota trading.